Integrating Ukhuwah Islamiyah Values in Waqf Asset Development within Islamic Boarding Schools - Eko Nur Cahyo; Dwi Hanif Febriansyah; Syamsuri Syamsuri (Ahlussunnah: Journal of Islamic Education, 2026)
The challenges of waqf management in the contemporary era require a paradigm shift that is not solely oriented toward economic aspects, but also integrates spiritual and social values in Islam. In this context, Islamic boarding schools (pesantren) have strategic potential as institutions that develop productive waqf based on Islamic values. This study aims to analyze the role of ukhuwah Islamiyah values embedded in the Panca Jiwa of Pondok Modern Darussalam Gontor in managing waqf assets. This research employs a qualitative method with a case study approach to explore the implementation of these values within the institutional context. The results indicate that ukhuwah Islamiyah functions as both a philosophical and practical foundation in waqf asset management, as reflected in the establishment of strong solidarity among the waqf board, institutional leaders, teachers, students, and alumni. These values contribute to the creation of a fair, transparent, and sustainable distribution system of waqf returns. Furthermore, the internalization of ukhuwah Islamiyah strengthens social cohesion and supports the sustainability of collective waqf asset management and development. These findings suggest that the integration of Islamic values in waqf management not only reinforces spiritual dimensions but also enhances the effectiveness and sustainability of waqf asset management within Islamic boarding school institutions.